Modulatory Role of Hesperetin–Copper(II) on Gut Microbiota in Type 2 Diabetes Mellitus Mice - Xi Peng; Yushi Wei; Deming Gong; Guowen Zhang (Foods, 2025)
Background: Exploring new strategies to improve type 2 diabetes mellitus (T2DM) is one of the frontier hotspots in the field of healthy food. Flavonoid–metal complexes have become one of the research hotspots in the field of health foods due to their unique structural and functional properties. Methods: In this study, the effect of hesperetin–copper(II) complex [Hsp–Cu(II)] on the gut microbiota of mice with T2DM was investigated by the 16S rRNA high-throughput sequencing. Results: The analyses of α and β diversity indicated that the richness and diversity of gut microbiota in the T2DM mice decreased and the community structure was significantly different from the normal mice. Hsp–Cu(II) increased the abundances of the beneficial bacteria (Lactobacillus, Ligilactobacillus, Romboutsia, Faecalibaculum, and Dubosiella), and decreased the amounts of the harmful bacteria (Desulfobacterota, Corynebacterium, and Desulfovibrio) and the ratio of Firmicutes/Bacteroidetes (from 44.5 to 5.8) in the T2DM mice, which was beneficial for regulating the composition of intestinal microbiota. The linear discriminant analysis effect size analysis showed that the intervention of Hsp–Cu(II) made the short-chain fatty acid (SCFA) producers (o_Lachnospirales, f_Lachnospiraceae, g_Faecalibaculum, g_Romboutsia, and g_Turicibacter) and the lactic acid bacteria producers (f_Lactobacillaceae and o_Lactobacillales) highly enriched, and the production of its metabolite SCFAs (acetic acid, propionic acid, butyric acid, and valeric acid) were increased in a dose-dependent manner, promoting the SCFA metabolism. Conclusions: Hsp–Cu(II) may improve glucose metabolic disorders and alleviate T2DM by modulating gut microbiota composition, promoting probiotics proliferation and SCFAs production, restoring intestinal barrier integrity, and suppressing local inflammation. These research findings may provide a theoretical basis for developing Hsp–Cu(II) as a new hypoglycemic nutritional supplement, and offer new ideas for the dietary food nutritional regulation to alleviate T2DM.